Effect of Surface Structure and Adsorption Activity on Implanting of b-Oriented ZSM-5 Zeolite Film on Modified α-Quartz Substrate - Chu, Ruizhi; Yang, Deguang; Meng, Xianliang; Yu, Shi; Wan, Yongzhou; Wu, Jiaxing; Wang, Jian (Frontiers in Chemistry, 2019)
b-oriented ZSM-5 zeolite film was synthesized on the macropore α-quartz substrate modified with titanium dioxide (TiO2), polyvinyl acetate (PVA) and chitosan (CTS) by hydrothermal crystallization. By comparing the binding energy and b-oriented angle of zeolite film on each modified α-quartz substrate, the orientations and combinations derived from structure-adsorption relationship were investigated with Material Studio simulation. Furthermore, the effects of calcination temperature and ultraviolet (UV) irradiation time on the surface structure and adsorption activity of TiO2 coating were studied. The increase adsorption potential energy and the formation of Ti-O-Si bind between zeolite crystal phase and substrate facilitate the continuous and uniform zeolite film growth. The TiO2 interlayer with anatase phase after UV irradiation presents a smooth surface with high Ti-OH density, consequently to high selectivity of b-orientation growth for the ZSM-5 crystals. Compared with the traditional ZSM-5, the higher stability has been exhibited with b-oriented ZSM-5 film /TiO2/α-quartz in the MTA reaction, and the methanol conversion and BTX selectivity remained higher than 90 % and 70 %, after 6 h reaction.